POPULATION INCOME IN UZBEKISTAN AND ANALYSIS OF FACTORS AFFECTING IT - Iskandarova Dilafruz Ikrom kizi (Labor economics and human capital, 2024)
In this article, indicators determining the quality of life of the population in Uzbekistan, increasing the income of the population and the factors affecting it are analyzed. Factors such as expected years of education, number of employed population and expenses allocated to the social sector from the state budget were selected as factors affecting the income of the population, and their influence and importance studied by correlation coefficient and regression equation. Conclusions and suggestions are given based on the results of the econometric model.